Numerical Analysis of Wind Turbine Airfoil Aerodynamic Performance with Leading Edge Bump. (22nd February 2015) - Asli, Majid; Mashhadi Gholamali, Behnam; Mesgarpour Tousi, Abolghasem
Abstract : Aerodynamic performance improvement of wind turbine blade is the key process to improve wind turbine performance in electricity generated and energy conversion in renewable energy sources concept. The flow behavior on wind turbine blades profile and the relevant phenomena like stall can be improved by some modifications. In the present paper, Humpback Whales flippers leading edge protuberances model as a novel passive stall control method was investigated on S809 as a thick airfoil. The airfoil was numerically analyzed by CFD method in Reynolds number of 10 6 and aerodynamic coefficients in static angle of attacks were validated with the experimental data reported by Somers in NREL. Therefore, computational results for modified airfoil with sinusoidal wavy leading edge were presented. The results revealed that, at low angles of attacks before the stall region, lift coefficient decreases slightly rather than baseline model. However, the modified airfoil has a smooth stall trend while baseline airfoil lift coefficient decreases sharply due to the separation which occurred on suction side. According to the flow physics over the airfoils, leading edge bumps act as vortex generator so vortices containing high level of momentum make the flow remain attached to the surface of the airfoil at high angle of attack and prevent it from having a deep stall.